KETERKAITAN RASIO LANCAR DAN LABA PER SAHAM PADA BETA SAHAM DI PERUSAHAAN PERBANKAN - Susilawati, Deti; Fuadi, Fuadi; Sutihat, Sutihat (LP2M Universitas Bina Bangsa, 2024)
This research aims to analyze the influence of the current ratio and earnings per share on share beta in banking companies listed on the IDX in 2018-2022. The population in this study were banking companies registered on the IDX in 2018-2022 using annual financial report data taken by purposive sampling, resulting in 75 (seventy five) samples that met the criteria. The sampling criteria selected were 1) Banks registered on the IDX and PEFINDO 2018-2022. 2) Banks publish complete financial reports for the 2018-2022 period. 3) Banking produces positive profits consecutively for the 2018-2022 period. The analysis technique used is multiple linear regression analysis with a significance level of 5%, so the results of this study show that: 1) The current ratio has no effect on stock beta. 2) Earnings per share have a significant effect on stock beta